SEAWEED (Gracilaria sp.) AS A PHYTOREMEDIAN FOR WASTE WATER FROM INTENSIVE PONDS FOR VANAMEI SHRIMP (Litopenaeus vannamei) IN LUWU REGENCY - Patahiruddin, Patahiruddin; Muchlis, Andi Mi’rajusysyakur; Siswati, Siswati; Adam, M.; Ramadani, Nurmagfira (Universitas Mataram, 2025)
Sanitizing the water environment in vanamei shrimp (Litopenaeus vannamei) ponds will increase shrimp growth and improve the economy. Obstacles in aquaculture are the decreasing quality of production results and decreasing water quality. A biofilter is needed as a phytoremediation to reduce the high ammonia content from leftover feed and feces. The main component of this technology is seaweed (Gracilaria sp.) as a living technology that provides services in overcoming environmental problems. Therefore, phytoremediation technology can be used to manage nutrient and water dynamics; This can result in significant improvements in water quality as well as the restoration of degraded ecosystems. The aim of the research was to determine the effect of differences in density of Gracilaria sp. as a phytoremedian in the cultivation system to reduce the ammonia (NH3) content of shrimp pond wastewater in Batu Lotong, South Larompong District, Luwu Regency, South Sulawesi. The research used a completely randomized design (CRD) with 4 treatments and 3 repetitions. The results of measurements in the experiment showed that the highest ammonia (NH3) content in treatment D (0 g seaweed) ranged from 0.0074 mg/L - 0.0335 mg/L and the lowest in treatment A (100 g seaweed) ranged from 0.0032 mg/L-0.0335 mg/L. Specific growth rate of daily weight of seaweed Gracilaria sp. in treatment A (2.95%) per day, B (2.59%) per day, C (1.81%) per day, and D (0%) control / not given seaweed. This shows that the difference in density of the seaweed Gracilaria sp. as a phytomedian in the cultivation system, it has an effect on reducing the ammonia (NH3) content and the daily specific growth rate of the seaweed Gracilaria sp. The Anova statistical test shows that the seaweed Gracilaria sp has a real influence on reducing the ammonia (NH3) content in pond water (F.hit > f table 5%).